Ecological Disasters and Mental Health: Causes, Consequences, and Interventions - Morganstein, Joshua C.; Ursano, Robert J. (Frontiers in Psychiatry, 2020)
Ecological disasters highlight the importance of understanding natural disasters as they relate to a changing global climate. Such disasters often have a predictable pattern of evolving over time and anticipated psychological and behavioral problems and community disruptions. Various factors enhance transmission of these adverse effects beyond the geographic location of the ecological disaster, with certain populations being particularly vulnerable to these effects. Understanding the range and pattern of these effects can aid in optimizing interventions. The use of evidence-informed interventions can reduce distress, enhance well-being and improve functioning for affected individuals and communities. Effective preparedness involves an understanding of these factors, incorporation of them at all stages of disaster management, and continuous education and training for disaster planners and responders.